Catalytic improvement through collective leadership in Christian schools - Eckert, Jonathan (International journal of Christianity & education, 2025)
We examine collective leadership across seven conditions in public and Christian schools. We conducted a survey (n = 4525) of public (n = 2701) and Christian school (n = 1824) educators and compared the results to determine if there were significant differences. While responses were generally positive, we found differences in six of seven conditions with Christian schools reporting less positive results for supportive administration, work design, shared influence, and improvement. Christian schools were more positive about resources and supportive norms and working relationships. We discuss the implications of these findings for improving Christian schools.